The Impact of an Educational Module on Pharmacovigilance towards Improving Knowledge and Attitude of Nursing and Pharmacy Students - Manasa, Megaravalli Ramesh; Chandy, Sujith John; Pillai, Santosh Ramakrishnan (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Pharmacovigilance is an integral part of patient safety and rational use of medicines. It is the professional responsibility of not just physicians but also of other health care professionals who use medicines such as nurses and pharmacists. Therefore it is essential to create awareness about pharmacovigilance through an educational module during their undergraduate course. Objectives: 1. To evaluate the knowledge and attitude of nursing and pharmacy students towards pharmacovigilance. 2. Based on the above, to design an educational module on pharmacovigilance. 3. To assess the impact of the educational module on knowledge and attitude towards pharmacovigilance. Materials and Methods: A cross-sectional study was conducted on nursing and pharmacy students pursuing pharmacology. A structured validated questionnaire consisting of 20 questions was used to assess the baseline knowledge and attitude. An educational module was designed and imparted to the participants. After a two week period the impact of the educational module was assessed. Results: The educational intervention significantly improved the knowledge of the nursing and pharmacy students about pharmacovigilance. The students had a positive baseline attitude towards pharmacovigilance which did not change much after the educational module. Conclusion: The knowledge of the nursing and pharmacy students improved significantly after the educational intervention. This highlights the need for such an educational module during their learning period so as to imbibe the safety culture and reporting practice early on in a healthcare professional’s life. Periodical awareness activities for healthcare professionals to improve ADR reporting are however recommended for their sustained involvement in pharmacovigilance.
Keywords: Educational intervention; Learning; Pharmacovigilance; Nurses; Pharmacists